ADVANTAGES AND PROBLEMS OF TRANSITION TO INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS): UZBEKISTAN'S EXPERIENCE - Davlyatova Sayyora Gulamovna (Modern American Journals, 2025)
This article explores the benefits and challenges of adopting International Financial Reporting Standards (IFRS) in the context of Uzbekistan's transition towards international financial transparency. The study aims to identify how IFRS contributes to enhancing the reliability, comparability, and transparency of financial statements among local companies while also addressing the practical barriers faced during its implementation. Based on literature analysis and field data, the paper presents both theoretical and empirical insights into the adoption process and its impact on the accounting practices in Uzbekistan.
Keywords: IFRS, financial reporting, Uzbekistan, accounting reform, transparency, comparability, implementation challenges, standardization, economic development, convergence.